What's the influence of social interactions on substance use and treatment initiation? A prospective analysis among substance-using probationers. (February 2019) - Spohr, Stephanie A.; Livingston, Melvin D.; Taxman, Faye S.; Walters, Scott T.
Abstract: Introduction: A person's social environment greatly affects the likelihood of substance use, which in turn affects risk for criminal behavior. This study examined how people's social environment early in probation contributed to later substance use and treatment outcome, both of which predict probation success. Methods: Data were analyzed from a randomized controlled trial of substance-using probationers (N = 316). Moderation analyses assessed the relationship between social support near the start of probation and substance use and treatment initiation after 2 and 6 months. Results: Abstinence at 2-months was associated with better baseline measures of support quality (more positive support, fewer negative interactions, and reduced conflict). Similar associations were identified for 6-month abstinence including better baseline quality, more positive support, and less family and peer conflict. There were no significant associations between the baseline social support and treatment initiation at 2-months. However, poorer baseline quality support and more negative interactions predicted increased treatment initiation at 6-months. Conclusions: Social support and the quality of an offender's social network have important implications for substance use and treatment compliance. The criminal justice system emphasizes ways to minimize negative social influences among offenders (i.e., probation conditions that limit contact with other offenders). However, this study suggests that behavior change is a function of not only reducing negative influences but also increasing positive or good quality supports. Highlights: Abstinence was associated with better baseline measures of support quality. More positive support, few negative interactions and conflict predicted abstinence. Treatment was associated with poorer baseline measures of support quality. Poor quality support and more negative interactions predicted treatment initiation.